The Course of Endoscopic Treatment Success in Biliary Complications After Living Donor Liver Transplantation - Engin ATAMAN; Murat HARPUTLUOGLU; Yilmaz BILGIC; Yasir Furkan CAGIN; Mehmet Ali ERDOGAN; Ramazan KUTLU; Koray KUTLUTURK; Ibrahim ORMAN; Osman SAGLAM; Ali Riza CALISKAN (Medeniyet Medical Journal)
Objective: Our aim was to present the results of endoscopic retrograde cholangiopancreatography (ERCP) after living donor liver transplantation (LDLT) between February 2015 and June 2021. Methods: Clinical data included LDLT indications, time to perform ERCP after LDLT, number of ERCP procedures, indications for ERCP, and all treatment outcomes, including ERCP, percutaneous, and surgical interventions. We compared the obtained data with our previous study published by our team in 2018, which included 446 patients who underwent ERCP for biliary complications after LDLT between 2005 and 2015. Results: We performed ERCP in 283 of 1506 patients with LDLT who underwent duct-to-duct anastomosis during transplantation and then developed biliary complications. Our endoscopic success rates were 60.9% and 71.0% in the previous and present studies, respectively. Conclusions: Our findings suggest that the success rate of endoscopic treatment of biliary complications in patients with LDLT increases in correlation with the increasing experience of clinicians treating these patients.